An unusual dermoid cyst presenting as midline swelling of neck in an adult patient - Chaudhary, Pallavi; Mathur, Navneet P.; Silu, Manju (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Dermoid cysts are true hamartomas focal malformations that can resemble neoplasms grossly and even microscopically but they arise from an abnormal formation of tissue elements. Here we are presenting a 44 years old woman presented with a midline mass in the neck present for many years. Fine-needle aspiration biopsy showed single and anucleate squamous along with few mature squamous cells against the background of debris. No atypical cells were seen. Ultrasonical examination revealed well-defined thick-walled area in the midline measuring 37×27 mm. Histologic examination of the cystic content identified epidermis, sebaceous glands, and hair follicles along with copious sebaceous material. These findings are consistent with a dermoid cyst. So, our case report demonstrates that dermoid cysts can present as neck mass and must be kept in the differential diagnosis. Even though characteristic radiological and histopathological features make the diagnosis simple yet, it may be difficult to diagnose, if present at unusual locations.